Metasurface spatial filters for multiple harmonic signals - Kim Daeik; Nguyen Mai Anh; Byun Gangil; Lee Jongwon (Nanophotonics)
Nonlinear frequency mixings have shown an alternative way to create new electromagnetic sources in frequency ranges that are difficult to access with conventional techniques. To simultaneously use the fundamental frequency pump beam and multiple harmonic signals generated in the same channel, a device capable of separating each frequency component is required. Here, we propose and experimentally demonstrate metasurface-based spatial filters for the pump frequency and multiple harmonic frequencies. The metasurface was designed using eight different split ring resonator-based phase elements with 45° phase spacing, which allows wavefront shaping. The metasurface designed to have a one-dimensional gradient phase array produces cross-polarized reflection waves with different beam steering angles at the third- and fifth-harmonic frequencies (15 and 25 GHz) and operates as a metallic mirror at the fundamental frequency of 5 GHz. Our work suggests a new method to enable simultaneous use of broadband multi-frequency sources based on nonlinear frequency mixing.